2002
DOI: 10.1159/000048680
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Cognitive Improvement in Schizophrenics Treated with Typical and Atypical Neuroleptics

Abstract: Objective: Atypical neuroleptics seem to be more beneficial than typical ones with respect to long-term neuropsychological functioning. Thus, most studies focus on the long-term effects of neuroleptics. We were interested in whether atypical neuroleptic treatment is also superior to typical drugs over relatively short periods of time. Methods: We studied 20 schizophrenic patients [10 males, mean age 35.5 years, mean Brief Psychiatric Rating Scale (BPRS) score at entry 58.9] admitted to our hospital with acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 35 publications
0
18
1
2
Order By: Relevance
“…The absence of detrimental effects of low doses of haloperidol in control subjects and the demonstration of beneficial cognitive effects in patients by equivalent, low doses of haloperidol (Green et al, 2002;Harvey et al, 2005;Keefe et al, 2006b;Mishara and Goldberg, 2004;Remillard et al, 2005;Rollnik et al, 2002) together suggest that conclusions about the cognitive profile of FGAs require careful consideration of dose and receptor occupancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of detrimental effects of low doses of haloperidol in control subjects and the demonstration of beneficial cognitive effects in patients by equivalent, low doses of haloperidol (Green et al, 2002;Harvey et al, 2005;Keefe et al, 2006b;Mishara and Goldberg, 2004;Remillard et al, 2005;Rollnik et al, 2002) together suggest that conclusions about the cognitive profile of FGAs require careful consideration of dose and receptor occupancy.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, several studies indicated that members of both classes of antipsychotic drugs produce moderate and largely equivalent improvements in cognitive function, particularly when administered at relatively low doses (Green et al, 2002;Harvey et al, 2005;Keefe et al, 2006b;Mishara and Goldberg, 2004;Remillard et al, 2005;Rollnik et al, 2002). Thus, the goal of our research was to define an animal model capable of detecting the limited beneficial cognitive effects of low-dose treatment of an FGA (haloperidol) and an SGA (clozapine; see 'Methods' for the definition and justification of low doses of either drug; Kapur et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In general, modest cognitive benefits from antipsychotic medications are characterized by reduction of generalized cognitive deficits across a wide range of abilities, rather than particular effects on a specific neuropsychological domain (Buchanan et al, 1994;Cassens et al, 1990;Hill et al, 2004a;Rollnik et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Queste caratteristiche hanno permesso di aumentare la compliance del trattamento e di diminuire il numero di ricadute e di successive ospedalizzazioni [1,[17][18][19][20][21][22][23][24][25]. Peraltro non tutti sono concordi nel considerare gli atipici come la terapia di prima scelta nel trattare i soggetti affetti da schizofrenia [26].…”
Section: * Pharmes Studi DI Valutazione Economica Milanounclassified